What are the effects of diagnostic imaging on clinical outcomes in patients with low back pain presenting for chiropractic care: a matched observational study - Hazel J. Jenkins (BMC, 2021)
Abstract Background Evidence suggests that diagnostic imaging for low back pain does not improve care in the absence of suspicion of serious pathology. However, the effect of imaging use on clinical outcomes has not been investigated in patients presenting to chiropractors. The aim of this study was to determine if diagnostic imaging affects clinical outcomes in patients with low back pain presenting for chiropractic care. Methods A matched observational study using prospective longitudinal observational data with one year follow up was performed in primary care chiropractic clinics in Denmark. Data was collected from November 2016 to December 2019. Participants included low back pain patients presenting for chiropractic care, who were either referred or not referred for diagnostic imaging during their initial visit. Patients were excluded if they were less than 18 years old, had a diagnosis of underlying pathology, or had previous imaging relevant to their current clinical presentation. Coarsened exact matching was used to match participants referred for diagnostic imaging with participants not referred for diagnostic imaging on baseline variables including participant demographics, pain characteristics, and clinical history. Mixed linear and logistic regression models were used to assess the effect of imaging on back pain intensity and disability at two-weeks, three-months, and one-year, and on global perceived effect and satisfaction with care at two-weeks. Results 2162 patients were included, with 24.1% referred for imaging. Near perfect balance between matched groups was achieved for baseline variables except age and leg pain. Participants referred for imaging had slightly higher back pain intensity at two-weeks (0.4, 95%CI: 0.1, 0.8) and one-year (0.4, 95%CI: 0.0, 0.7), and disability at two-weeks (5.7, 95%CI: 1.4, 10.0), but the changes are unlikely to be clinically meaningful. No difference between groups was found for the other outcome measures. Similar results were found when sensitivity analysis, adjusted for age and leg pain intensity, was performed. Conclusions Diagnostic imaging did not result in better clinical outcomes in patients with low back pain presenting for chiropractic care. These results support that current guideline recommendations against routine imaging apply equally to chiropractic practice.